Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1974
DOI: 10.1021/ac60349a033
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hydrogen ion concentration on the determination of lead by solvent extraction and atomic absorption spectrophotometry

Abstract: of an isopotential point at Ed -0.03-0.05 V in the purified HCIO4, both in the successive cathodic and anodic disk potential scans. These IP's are surprisingly well developed. As has been shown by electrochemical mass spectrometry (38), an unknown organic impurity is adsorbed when the Pt disk electrode is held more cathodic than 0.5 V. This organic species can be desorbed simultaneously with the adsorption of strongly bonded adsorbed H, resulting in the IP in the cathodic scan. Seemingly, this impurity star… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
1

Year Published

1976
1976
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(9 citation statements)
references
References 12 publications
0
8
0
1
Order By: Relevance
“…Several extractants for the photometric determination of Au in complex materials have been reported (1)(2)(3)(4)(5)(6)(7)(8)(9)(10). These extractants possess a variety of structures, capable of forming ion pair complexes of Au with cyano, halo, nitrato, sulfato, and other anions providing a hydrophobic outer layer which facilitates its transfer to the organic phase.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several extractants for the photometric determination of Au in complex materials have been reported (1)(2)(3)(4)(5)(6)(7)(8)(9)(10). These extractants possess a variety of structures, capable of forming ion pair complexes of Au with cyano, halo, nitrato, sulfato, and other anions providing a hydrophobic outer layer which facilitates its transfer to the organic phase.…”
Section: Resultsmentioning
confidence: 99%
“…It was also reported for simultaneous extraction and spectrophotometric determination of Au, Pd, and Pt from halide media (7). Furthermore, thioorganic compounds, e.g., 2-mercaptobenzothiazole, pyrimidinethiol, and others, may be applied for the extraction and spectrophotometric determination of Au(III), but platinum metals seriously interfere (3,4,(8)(9)(10).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Em 1974, Everson e Parker demonstraram que íons metálicos presentes em metaloproteínas são os principais responsáveis pela adsorção dessas em resinas contendo quelantes imobilizados e exploraram esta afinidade na separação deste tipo de proteínas. 1 A técnica proposta por Everson e Parker popularizou-se com o trabalho publicado por Porath e colaboradores em 1975, quando os autores introduziram o termo cromatografia de afinidade por íons metálicos imobilizados (Immobilized Metal-Ion Affinity Chromatography -IMAC). 2 IMAC explora a interação entre espécies doadoras de elétrons presentes na superfície de biomoléculas em solução e íons metálicos quelatados imobilizados em um suporte sólido.…”
Section: Introductionunclassified
“…Ammonium pyrrolidined-ithiocarbamate (APDC) was first investigated by Malissa and Schoffmann in 1955. 1 The combination of APDC as a chelating agent and methyl isobutyl ketone (MIBK) as an organic solvent in atomic absorption spectrophotometry has been reported by a number of authors [2][3][4][5][6][7] and some 4,7 found it the most useful extraction system, because APDC forms stable chelates with numerous metal over a wide pH range and MIBK exhibits ideal combustion properties in the flame. A number of advantages results from the extraction of APDC-metal complexes into a suitable organic phase.…”
Section: Introductionmentioning
confidence: 99%